If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + -4x = 10 + -1x Solving 23 + -4x = 10 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 23 + -4x + x = 10 + -1x + x Combine like terms: -4x + x = -3x 23 + -3x = 10 + -1x + x Combine like terms: -1x + x = 0 23 + -3x = 10 + 0 23 + -3x = 10 Add '-23' to each side of the equation. 23 + -23 + -3x = 10 + -23 Combine like terms: 23 + -23 = 0 0 + -3x = 10 + -23 -3x = 10 + -23 Combine like terms: 10 + -23 = -13 -3x = -13 Divide each side by '-3'. x = 4.333333333 Simplifying x = 4.333333333
| 3x-2y=12 | | 21=2(2x+3)+2x | | 3x-22=8x+18 | | 7b^2-42b+56= | | 3x+5y=-5 | | 2x^2-6x-9=0 | | -1+6x+x=1 | | 18=2(2x+3)+2x | | 5x(2x+3)+2x(3x+1)= | | 15x-20y=-7 | | 4x+7=21 | | 4x+13=3x+15 | | s^2-10s+24= | | 2x-3y=16 | | 8(10x^2-3x-9)=(5x^2-4x+8)16 | | 2L+3(10)=440 | | 2(10x^2-3x-9)=4(5x^2-4x+8) | | 4Y-2=10 | | 11=2.2t | | y=10+5 | | 6a=0.96 | | (x-3)(x+4)=x^2+4 | | x^2-8x+8=0 | | -7y=28 | | 3(x^2+4x-2)=2(x^2-x+1)+x^2+34 | | 96-5x=40x+16 | | 9-9x=21-16x | | j-3=-7 | | -19-10x=7x+15 | | 4x+7=-77-10x | | 5x-8=4+x | | 121-3x=6x+13 |